Pengaruh Perilaku Kepemimpinan dan Pengalaman Kerja Kepala Sekolah terhadap Motivasi Berprestasi Guru Agama Islam di SMA Negeri Kota Jambi - Hazizah; Mahmud (JMiE (Journal of Management in Education), 2021)
This research aims to determine and analyze; (1) description of the principal's leadership behavior and the teacher's work experience towards the motivation of the achievement of religious teachers; (2) influence of the principal's leadership behavior on the motivation of teacher achievement; (3) the relationship between the teacher's work experience and the motivation of the teacher's performance; (4) Influence of the principal's leadership behavior and teacher work experience on the motivation of the teacher's religious achievement. The study used descriptive analysis survey methods, with a sample of 35 religious teachers and used correlation and regression analysis. The results of the study found that the magnitude of the simultaneous influence between the principal's leadership behavior (X1) and the teacher's work experience (X2) on the teacher's achievement motivation (Y) was 0.746 which was classified as weak. Meanwhile, the simultaneous contribution of the variables (X1) and (X2) to (Y) = R2 x100% or 0.7462 x 100% = 55.7% and the remaining 44.3% is determined by other variables. Then the rise and fall or the size of achievement motivation can be predicted through the regression equation: = 19.766 + 0.2213x1 + 0.9734x2. The results of this study can be drawn several sub-conclusions as follows: (1) the magnitude of the influence of the principal's leadership behavior variable (X1) on teacher achievement motivation (Y) is 0.606% while the contribution of the variable (X1) to (Y) is 36.72%. the remaining 63.28% is determined by other variables. (2) the magnitude of the influence of the teacher's work experience (X2) on the teacher's achievement motivation (Y) is 0.746% while the contribution of the variable (X2) to (Y) is 55.65% and the remaining 44.35% is determined by other variables. (3) the magnitude of the relationship between principal leadership behavior (X1) and teacher work experience (X2) is 0.609 then the contribution of variables (X1) and (X2) is 37.09% while the remaining 52.25%.